The Position of Institutional Law on Halal Product Assurance in the Sharia Perspective Towards Society 5.0 - Soegianto Soegianto; Retno Widyani (Ann Publisher, 2024)
The socialization of the institutional legal position of Halal Product Assurance (JPH) in the perspective of Sharia Society 5.0 was carried out at the UIN Purwokerto Postgraduate Program on October 10, 2023. The purpose of this charity activity is to raise public awareness. The socialization materials presented included laws and regulations such as the Job Creation Law, the Halal Product Guarantee Law, the Consumer Protection Law, and the Government Law that regulates the Halal Product Guarantee industry. In the field of cosmetics, JPH also issued Halal certification for PT Diera Muatiara Internasional facial care products from LPPOM MUI. This public relations campaign shows that legal certainty is needed to guarantee halal products, and the quality of halal products in circulation is very important to protect consumers. Companies that produce and sell halal products have the added advantage of having a guarantee of halal products.